Patterns and determinants of small‐quantity LNS utilization in rural Malawi and Mozambique: considerations for interventions with specialized nutritious foods. Issue 1 (19th January 2016) - Kodish, Stephen R.; Aburto, Nancy J.; Nseluke Hambayi, Mutinta; Dibari, Filippo; Gittelsohn, Joel
Abstract: Small‐quantity, lipid‐based nutrient supplements (SQ‐LNS) show promise to improve the quality of maternal and child diets, particularly during the first 1000 days of life. The potential of SQ‐LNS to impact positively upon nutritional status relies on numerous factors, including complementary dietary intake, disease prevalence and dynamics of household utilization, including sharing practices. Therefore, this study sought to elucidate the patterns and determinants of SQ‐LNS utilization among children 6–23 months and potential sharing practices of other household members prior to intervention development. In Ntchisi, Malawi and Cabo Delgado, Mozambique, both rural, agricultural settings, we conducted two home‐feeding trials of 8 and 6 weeks, respectively, nested within a larger multi‐phase, emergent formative research design. Multiple methods, including in‐depth interviews ( n = 38), direct meal observations ( n = 80), full‐day child observations ( n = 38) and spot checks of SQ‐LNS supply ( n = 23), were conducted with households ( n = 35 in Malawi; n = 24 in Mozambique). Overall, the SQ‐LNS was utilized contrary to its recommended use, with 50% of households in Malawi reporting running out of stock too early and 87% of households in Mozambique either overusing or underusing the product. Utilization of SQ‐LNS was manifested in four patterns of overuse and two of underuse and was determined by factors at multiple levels of influence. Maternal and child health efforts need to consider the reasons behind choices by households to overuse or underuse SQ‐LNS and design intervention strategies to increase the likelihood of its appropriate utilization.